Preparation method of ammonia production material MIL-101 (Cr)-NO2rGQDs through photocatalytic nitrate reduction

By combining graphene quantum dots with MIL-101(Cr)-NO2 composite material to form MIL-101(Cr)-NO2/r-GQDs composite material, the problem of complex and cost-effective preparation of photocatalytic nitrate reduction ammonia in the prior art is solved, and an efficient, economical and environmentally friendly photocatalytic nitrate reduction ammonia is achieved.

CN119869615APending Publication Date: 2025-04-25HANGZHOU NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510062067.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, when preparing ammonia-making materials for photocatalytic nitrate reduction, there are problems such as complex preparation methods, high cost and low spectral utilization, and it is difficult to achieve economical and environmentally friendly ammonia-making methods.

Method used

MIL-101(Cr)-NO2 is used as a support, and combined with graphene quantum dots (GQDs) through self-assembly technology to form MIL-101(Cr)-NO2/r-GQDs composite material, and a method of photocatalytic nitrate reduction is used to prepare ammonia.

Benefits of technology

It has achieved high efficiency in photocatalytic nitrate reduction of ammonia, and has the characteristics of simple synthesis method, convenient operation, good light stability, green and environmentally friendly, and excellent photocatalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869615A_ABST
    Figure CN119869615A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ammonia production through photocatalytic reduction of nitrate radicals, and discloses a preparation method of a material MIL-101 (Cr)-NO2rGQDs for ammonia production through photocatalytic reduction of nitrate radicals, the compound is a novel catalytic material in the field of ammonia production through photocatalytic reduction of nitrate radicals, the NH4 < + > generation rate of the compound reaches 37.99 mmol / gcat. / h under the irradiation of ultraviolet light (100mW / cm < 2 >), and the selectivity of ammonia production through reduction of nitrate radicals reaches 88.97%; under the irradiation of visible light, the generation rate of NH4 < + > is 24.61 mmol / gcat. / h, and the selectivity of reducing nitrate radicals into ammonia reaches 87.41%; the generation rate of NH4 < + > under infrared light can reach 8.73 mmol / gcat. / h, and the selectivity of reducing nitrate radicals into ammonia reaches 88.12%. According to the method, MOF is taken as a carrier, filling of r-GQDs in a cavity of the MOF is realized through a self-assembly technology, and a series of r-GQDs / MOF photocatalytic compounds are obtained. The porous structure of the MOF material enables nitrate radicals to be enriched on the surface of the catalyst, the binding efficiency between reactants and the catalyst is improved, industrial wastewater containing nitrate is used as a raw material, valuable ammonia can be collected, and the method has important significance in industrial production, economic and green ammonia production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalytic materials, and in particular to a method for preparing a photocatalytic nitrate reduction ammonia production material MIL-101(Cr)-NO2rGQDs. Background Art

[0002] Ammonia (NH3) is an irreplaceable chemical raw material in human production and life. It is the raw material for nitrogen fertilizers, plastics, medicines, explosives, synthetic fibers, resins and printing and dyeing. According to statistics, by 2050, the annual growth rate of ammonia production capacity is expected to reach 40% (>200 million tons). At present, the main technology used for ammonia is the Haber-Bosch process (350-550℃, 15-25MPa), which has been recognized as an energy-intensive synthesis method (consuming about 5.50EJ / year) and has higher carbon emissions (450 million tons / year CO2). Therefore, exploring a new economic An economically and environmentally friendly ammonia production strategy is imminent; in this context, nitrate reduction to produce ammonia was proposed, which is a route to turn waste (nitrate) into treasure (ammonia); it is well known that nitrate pollution has become a global groundwater environmental problem and endangers people's health in direct or indirect ways, such as causing methemoglobinemia in infants; in the solar spectrum, ultraviolet (UV) is only 4%, while the near-infrared band (about 96%) is the visible light and near-infrared band; how to improve the utilization rate of the visible light spectrum and broaden the spectral response range is the focus and difficulty of current research.

[0003] In recent years, graphene quantum dots (GQDs) have attracted more and more researchers with their unique physicochemical properties and multi-field applications. Compared with traditional semiconductors, GQDs are greener, more economical and photostable. High-quality GQDs have excellent optical properties, such as wide-band response and various types of fluorescence, making them suitable for multiple scenarios, such as bioimaging, LED lights and photocatalysis. However, despite having so many advantages, the exciton excitation energy of pure GQDs is relatively high, resulting in their low photocatalytic nitrate reduction efficiency. Strategies that can effectively regulate the electron density of the complex and optimize its optical, conductivity and transport properties by properly selecting the substrate and using it to synthesize the catalyst have been proven. Therefore, in order to improve the effect of photocatalytic nitrate reduction, it is very critical to use other suitable substances as carriers of GQDs.

[0004] Metal organic frameworks (MOFs) have large specific surface area, high porosity and uniform porous structure, and have multiple excellent properties, showing great potential in photocatalysis, lithium-ion batteries, gas adsorption and separation. Mesoporous MOFs have attracted widespread attention due to their versatility. Due to the unique structure and adjustable porosity of MOFs, their properties can be more accurately adjusted and their functions optimized, and they have good prospects in many applications, such as the adsorption and separation of gases and hydrocarbons. Therefore, we proposed a preparation method for the photocatalytic nitrate reduction ammonia production material MIL-101(Cr)-NO2rGQDs. Summary of the invention

[0005] 1. Technical issues to be solved

[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing a photocatalytic nitrate reduction ammonia production material MIL-101(Cr)-NO2rGQDs, which has the advantages of simple preparation method, suitability for industrial production, good repeatability, simple reaction conditions and low cost.

[0007] (II) Technical solution

[0008] In order to achieve the purpose of the above-mentioned preparation method being simple, suitable for industrial production, having good repeatability, simple reaction conditions and low cost, the present invention provides the following technical scheme: A preparation method of a photocatalytic nitrate reduction ammonia production material MIL-101(Cr)-NO2rGQDs, comprising the following steps:

[0009] S1. Preparation of MIL-101 (Cr): dissolve terephthalic acid and Cr(NO3)3·9H2O in deionized water in a certain proportion, dissolve them completely by ultrasonic treatment, then add 37%wt of HF and stir evenly, transfer the mixed solution to a 50mL polytetrafluoroethylene-lined reactor, and then place the reactor at 200°C to 250°C for 7 to 9 hours; after the reaction, cool the reactor naturally to room temperature, wash with N,N-dimethylformamide (DMF), water and ethanol three times respectively, then collect the product by centrifugation, and dry it at 50°C to 100°C in a vacuum environment for 10 to 15 hours to obtain MIL-101 (Cr);

[0010] S2. Preparation of MIL-101(Cr)-NO2: adding a certain proportion of MIL-101(Cr) to a mixture of concentrated H2SO4 and concentrated HNO3, stirring the mixture at 1°C to -2°C for 5 to 7 hours, pouring the mixture into ice water while stirring, and warming it to room temperature; washing the mixture with water and ethanol three times each, collecting the product by centrifugation, and drying it at 50°C to 100°C under vacuum for 10 to 15 hours to obtain MIL-101(Cr)-NO2;

[0011] S3, preparation of r-GQDs: glucose is added to deionized water in a certain proportion to dissolve, and after dissolution, the solution is transferred to a reactor with a polytetrafluoroethylene liner, and reacted at 150°C to 200°C for 4 to 5 hours; after the reactor is cooled, the collected solution is centrifuged to remove the precipitate, and the supernatant is poured into a beaker, a certain proportion of sodium borohydride is added, and the r-GQDs solution is obtained by stirring and reducing with a magnetic stirrer at room temperature for 3 to 5 hours;

[0012] S4. Preparation of r-GQDs / MIL-101(Cr)-NO2: Take an appropriate amount of MIL-101(Cr)-NO2 and add it to the pretreated rGQDs solution with a pH value of 7 to 8, and then stir it at room temperature for 3 to 5 hours; after the reaction is completed, centrifuge it, then wash it twice with deionized water, and finally vacuum dry it at 60°C to 100°C for 10 to 13 hours to obtain the desired product.

[0013] Preferably, the mass ratio of terephthalic acid to Cr(NO3)3·9H2O is 1:2 to 1:3.

[0014] Preferably, the molar ratio of the ML-101(Cr) to the mixed solution of concentrated H2SO4 and concentrated HNO3 is 1:200 to 1:250.

[0015] Preferably, the mass ratio of sodium borohydride to glucose is 1:5 to 1:10.

[0016] Preferably, the mass ratio of the MIL-101(Cr)-NO2 to rGQDs is between 1:3 and 1:8.

[0017] (III) Beneficial effects

[0018] Compared with the prior art, the present invention provides a method for preparing a photocatalytic nitrate reduction ammonia production material MIL-101(Cr)-NO2rGQDs, which has the following beneficial effects:

[0019] The preparation method of the photocatalytic nitrate reduction ammonia material MIL-101(Cr)-NO2rGQDs, the synthesized MIL-101(Cr)-NO2 / r-GQDs composite material is an exploration of obtaining a composite by self-assembly technology using MOF as a carrier, which is different from the traditional Haber-Bosch method for ammonia production, and utilizes photocatalytic nitrate reduction to produce ammonia, and has the characteristics of simple synthesis method, convenient operation, good photostability, green environmental protection, excellent photocatalytic performance, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 TEM and SEM images of the MOF of the present invention and TEM and SEM images of MOF / r-GQDs-2.9%;

[0021] Figure 2 This is a high-resolution image of 2.9% r-GQD / MOF prepared in the present invention;

[0022] Figure 3 XRD images of MOF and r-GQDs / MIL-101(Cr)-NO2 prepared in the present invention;

[0023] Figure 4 It is the XPS peak diagram of MOF and MOF / r-GQDs-2.9% of the present invention;

[0024] Figure 5 The r-GQDs / MOF prepared in the present invention has (a) photocatalytic nitrate reduction performance under three light sources and (b) selectivity (ce) stability spectrum;

[0025] Figure 6 The EDS image of MOF / r-GQDs-2.9% of the present invention and its element distribution diagram;

[0026] Figure 7 This is a series of N2 adsorption-desorption isotherms of TiOx / MOF collected at 77K in the present invention. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention and the accompanying drawings to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Embodiment 1:

[0029] See also Figure 1-7A method for preparing a photocatalytic nitrate reduction ammonia production material MIL-101(Cr)-NO2rGQDs comprises the following steps:

[0030] S1. Preparation of MIL-101 (Cr): dissolve terephthalic acid and Cr(NO3)3·9H2O in deionized water in a certain proportion, dissolve them completely by ultrasonic treatment, then add 37%wt of HF and stir evenly, transfer the mixed solution to a 50mL polytetrafluoroethylene-lined reactor, and then place the reactor at 200°C to 250°C for 7 to 9 hours; after the reaction, cool the reactor naturally to room temperature, wash with N,N-dimethylformamide (DMF), water and ethanol three times respectively, then collect the product by centrifugation, and dry it at 50°C to 100°C in a vacuum environment for 10 to 15 hours to obtain MIL-101 (Cr);

[0031] S2. Preparation of MIL-101(Cr)-NO2: adding a certain proportion of MIL-101(Cr) to a mixture of concentrated H2SO4 and concentrated HNO3, stirring the mixture at 1°C to -2°C for 5 to 7 hours, pouring the mixture into ice water while stirring, and warming it to room temperature; washing the mixture with water and ethanol three times each, collecting the product by centrifugation, and drying it at 50°C to 100°C under vacuum for 10 to 15 hours to obtain MIL-101(Cr)-NO2;

[0032] S3, preparation of r-GQDs: glucose is added to deionized water in a certain proportion to dissolve, and after dissolution, the solution is transferred to a reactor with a polytetrafluoroethylene liner, and reacted at 150°C to 200°C for 4 to 5 hours; after the reactor is cooled, the collected solution is centrifuged to remove the precipitate, and the supernatant is poured into a beaker, a certain proportion of sodium borohydride is added, and the r-GQDs solution is obtained by stirring and reducing with a magnetic stirrer at room temperature for 3 to 5 hours;

[0033] S4. Preparation of r-GQDs / MIL-101(Cr)-NO2: Take an appropriate amount of MIL-101(Cr)-NO2 and add it to the pretreated rGQDs solution with a pH value of 7 to 8, and then stir it at room temperature for 3 to 5 hours; after the reaction is completed, centrifuge it, then wash it twice with deionized water, and finally vacuum dry it at 60°C to 100°C for 10 to 13 hours to obtain the desired product.

[0034] Furthermore, the mass ratio of terephthalic acid to Cr(NO3)3·9H2O is 1:2 to 1:3.

[0035] Furthermore, the molar ratio of the ML-101(Cr) to the mixed solution of concentrated H2SO4 and concentrated HNO3 is between 1:200 and 1:250.

[0036] Furthermore, the mass ratio of sodium borohydride to glucose is 1:5 to 1:10.

[0037] Furthermore, the mass ratio of the MIL-101(Cr)-NO2 to rGQDs is between 1:3 and 1:8.

[0038] Embodiment 2:

[0039] This example aims to discuss in detail the preparation process of the r-GQDs / MIL-101(Cr)-NO2 composite material and its application in photocatalytic nitrate reduction to ammonia. Through self-assembly technology, the efficient filling of r-GQDs in the pores of MIL-101(Cr)-NO2 is achieved, which not only improves the material's ability to enrich nitrate, but also significantly enhances its photocatalytic activity. The specific preparation method is as follows:

[0040] First, 332 mg of terephthalic acid and 800 mg of Cr(NO3)3·9H2O were completely dissolved in 14 mL of deionized water by ultrasonic treatment; then, 0.1 mL (37% wt) of HF was added and stirred evenly, and then the mixed solution was transferred to a 50 mL polytetrafluoroethylene-lined reactor; next, the reaction was carried out at 220°C for 8 hours; after the reaction was completed, it was naturally cooled to room temperature; then, it was washed three times with N,N-dimethylformamide (DMF), water and ethanol respectively, and the product was collected by centrifugation at a centrifuge speed of 8000 r / min; finally, it was dried at 60°C in a vacuum environment for 12 hours;

[0041] Next, 100 mg ML-101 (Cr) was added to a mixture of 7 mL of concentrated H2SO4 and 5 mL of concentrated HNO3, and then stirred at 0°C for 6 hours; then the mixture was poured into 50 mL of ice water while stirring, and the mixture was heated to room temperature; the mixture was washed three times with water and ethanol, respectively, and then centrifuged at a speed of 8000 r / min to obtain a green crystalline product; finally, it was dried in a vacuum environment at 60°C for 12 hours;

[0042] Then, first, 540 mg of glucose was added to 40 mL of deionized water to dissolve, and then the solution was transferred to a reactor with a volume of 50 mL of polytetrafluoroethylene liner and reacted at 190°C for 3 hours; after the reactor was cooled to room temperature, the crude product collected was a brown-yellow solution with a caramel smell; then centrifuged at a speed of 11000 r / min for 1 hour to remove the precipitate, and the supernatant was the graphene quantum dot solution; the supernatant was poured into a beaker, 80 mg of sodium borohydride was added, and the solution was reduced by stirring with a magnetic stirrer at room temperature for 4 hours to obtain a reduced graphene quantum dot solution (i.e., r-GQDs solution);

[0043] Finally, take an appropriate amount of MIL-101(Cr)-NO2 and add it to the pretreated rGQDs solution with a pH value of 7, and then stir it for 4 hours at room temperature; when the reaction is completed, centrifuge it at 8000r / min, then wash it twice with deionized water, and finally vacuum dry it at 80°C for 12 hours.

[0044] In this example, 200 mg, 150 mg, 100 mg and 50 mg of MIL-101(Cr)-NO2 were added, respectively, and recorded as MIL-101(Cr)-NO2 / r-GQDs-2.1%, MIL-101(Cr)-NO2 / r-GQDs-2.9%, MIL-101(Cr)-NO2 / r-GQDs-3.4% and MIL-101(Cr)-NO2 / r-GQDs-4.2%, respectively. The MOF mentioned in this example refers to MIL-101(Cr)-NO2.

[0045] The experimental results show that Figure 1 As shown, the TEM and SEM images of MOF show that it has a regular octahedral structure with a size of about 300-400nm; compared with MOF, the size of MOF / r-GQDs-2.9% does not change much; the scanning image shows that the surface of the MOF / rGQDs-2.9% sample is smooth, without quantum dot loading, and the graphene quantum dots are mainly loaded in the internal confinement of MOF.

[0046] This example uses energy dispersive X-ray (EDS) analysis to study the distribution of each element in MOF / rGQDs-2.9%; Figure 6 As shown, it can be observed that elements such as C, N, Cr and O present a consistent and balanced distribution on the sample. The graphene quantum dots are evenly dispersed in the MOF material, which helps to achieve effective electron transfer.

[0047] In order to have a clear understanding of the microstructure of the material, this embodiment conducted a high-resolution test on the material, as shown in the accompanying drawings of the specification. Figure 2 As shown in the figure, the pore distribution of MOF can be seen. It is found that the pore distribution near the edge of MOF is relatively clear, while the pore distribution in the area where graphene quantum dots exist gradually becomes blurred. This shows that after the graphene quantum dots are filled into the MOF cavity, the crystallinity of MOF is changed to a certain extent.

[0048] This example also analyzes the N2 adsorption-desorption isotherms of the MOF / rGQDs structure at 77K, and observes how its BET surface area changes with pressure; Figure 7 As shown, the N2 adsorption-desorption isotherm belongs to type IV, which means that there is a mesoporous structure in the skeleton. When the content of graphene quantum dots gradually increases, the corresponding N2 absorption will decrease accordingly.

[0049] This embodiment also studies the crystal structure of the catalyst by using XRD; Figure 3 As shown, it shows the XRD images of MOF / r-GQDs samples prepared after each input of materials; these data show that the signal peak of MOF is consistent with the standard; comparing the samples obtained before and after the combination of MOF and r-GQDs, although their diffraction intensities are different, the positions of their diffraction peaks remain consistent, indicating that the addition of r-GQDs has no effect on the MOF lattice structure; while r-GQDs have a significant bulge at about 30°, which suggests that it is an amorphous graphene quantum dot;

[0050] In this embodiment, by analyzing the functional groups of MIL-101(Cr)-NO2, r-GQDs, and MIL-101(Cr)-NO2 / r-GQDs, it is found that the vibration peaks of water and -OH in the pores of the material are located at 3430 cm-1 and 1606 cm-1, respectively, which makes it have good hydrophilicity and good stability; in addition, the vibration peak of C=O of free terephthalic acid in MOF is located at 1696 cm-1, the stretching peak of aromatic C=C at 1501 cm-1, and the characteristic vibration of OCO group at about 1400 cm-1, these peaks are attributed to the presence of dicarboxylic acid ligands; the deformation vibration of CH at 1012 and 743 cm-1, the symmetric stretching vibration of Cr-O at 577 cm-1 and MIL-101(Cr)-NO2 / r-GQDs ... consistent; in r-GQDs, 3430cm-1 represents C-OH, 1650cm-1 represents the stretching vibration of C=C, and the weak peaks at 1084 and 2907cm-1 represent the stretching vibrations of CO and CH respectively; consistent with the characteristic peaks of r-GQDs; although its main peak is very similar to MIL-101(Cr)-NO2 in its original state, the entire MIL-101(Cr)-NO2 architecture after mixing can still remain stable; in particular, this embodiment found that in this process, although r-GQDs were introduced into the system and combined, it did not damage the structure of MIL-101(Cr)-NO2; on the contrary, its presence only slightly changed the crystallinity of the substance - this result can be seen from the attached figure of the specification Figure 3 It can be confirmed above.

[0051] This embodiment also studies the surface element composition and chemical state of the catalyst by using XPS; Figure 6 It can be seen that the main components of MOF / r-GQDs are C, N, O and Cr, while the N element has not changed significantly; Figure 6 The peaks at 284.6 eV and 288.6 eV represent the CC bond and the O=CO bond; similarly, Figure 6 The cO1s part, 533.7eV represents CO, and 531.7eV represents the Cr-O bond; as shown in the attached figure of the specification Figure 6 As shown, the Cr2p spectrum in MOF / rGQDs-2.9% dissociates into two spin orbits between the binding energy of about 577.1eV and 586.7eV, which are Cr3+-2p3 / 2 and Cr3+-2p1 / 2, respectively, both representing Cr3+-O within the internal metal clusters of MIL-101(Cr)-NO2.

[0052] This example also tested the photocatalytic nitrate reduction function of MOF / r-GQDs series of materials under ultraviolet light, visible light and infrared light; the results showed that MOF / rGQDs-2.9% showed the best photocatalytic nitrate reduction ability among all these light sources; from the attached drawings of the specification Figure 5 It can be seen from a and b that when irradiated with ultraviolet light (100mW / cm2), the NH4+ generation rate is 37.99mmol / gcat. / h, and the selectivity of nitrate reduction to ammonia reaches 88.97%; under visible light irradiation, the NH4+ generation rate is 24.61mmol / gcat. / h, and the selectivity of nitrate reduction to ammonia reaches 87.41%; under infrared light, the ammonia generation rate can reach 8.73mmol / gcat. / h, and the selectivity of nitrate reduction to ammonia reaches 88.12%, as shown in the attached figure of the specification. Figure 5 As shown in c, d, and e, this article further tested the catalyst stability, and the catalyst also showed good stability.

[0053] In this embodiment, MOF is used as a carrier, and r-GQDs are filled in its cavity through self-assembly technology, so as to obtain a series of r-GQDs / MOF photocatalytic composites; since r-GQDs are completely embedded in the pores of MOF, this greatly improves the photon transmission efficiency between the two, while reducing the interaction between electrons and holes, greatly improving the catalytic effect and spectral absorption range of nitrate conversion to ammonia during the photocatalytic process; MOF / rGQDs-2.9% is the best product in the synthetic ammonia reaction of catalyzing nitrate conversion, and it can achieve an NH4+ generation rate of 37.99; mmol / gcat. / h under ultraviolet light (100; mW / cm2), and the selectivity of nitrate reduction to ammonia reaches 88.97%; under visible light irradiation, the NH4+ generation rate is 24.61; mmol / gcat. / h, and the selectivity of nitrate reduction to ammonia reaches to 87.41%; the NH4+ generation rate under infrared light can reach 8.73; mmol / gcat. / h, and the selectivity of nitrate reduction to ammonia reaches 88.12%; MOF; the porous structure of the material itself makes nitrate enriched on the catalyst surface, improving the binding efficiency between the reactants and the catalyst; at the same time, since r-GQDs are highly distributed in the pores of MOF, this greatly affects the photocatalytic performance of the MIL-101(Cr)-NO2 / r-GQDs composite material; this distribution method helps to achieve efficient separation and transmission between photogenerated electrons and holes, thereby greatly improving the photocatalytic reduction effect of nitrate and expanding the light absorption area; from the perspective of microstructure and interface, r-GQDs are tightly embedded in MOF, and the presence of sp2 bonds makes it more suitable for photoreduction reactions and this catalyst also has excellent light stability.

[0054] In summary, the preparation method of the photocatalytic nitrate reduction ammonia production material MIL-101(Cr)-NO2rGQDs and the synthesized MIL-101(Cr)-NO2 / r-GQDs composite material are an exploration of obtaining a composite by self-assembly technology using MOF as a carrier. It is different from the traditional Haber-Bosch method for ammonia production, and utilizes photocatalytic nitrate reduction to produce ammonia. It has the characteristics of simple synthesis method, convenient operation, good photostability, green environmental protection, and excellent photocatalytic performance.

[0055] The relevant modules involved in this system are all hardware system modules or functional modules that combine computer software programs or protocols with hardware in the prior art. The computer software programs or protocols involved in the functional modules are themselves technologies that are well known to those skilled in the art and are not improvements of this system. The improvements of this system are the interaction or connection relationships between the modules, that is, improvements to the overall structure of the system to solve the corresponding technical problems to be solved by this system.

[0056] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a photocatalytic nitrate reduction ammonia production material MIL-101(Cr)-NO2rGQDs, characterized in that: The following steps are involved: S1. Preparation of MIL-101 (Cr): dissolve terephthalic acid and Cr(NO3)3·9H2O in deionized water in a certain proportion, dissolve them completely by ultrasonic treatment, then add 37%wt of HF and stir evenly, transfer the mixed solution to a 50mL polytetrafluoroethylene-lined reactor, and then place the reactor at 200°C to 250°C for 7 to 9 hours; after the reaction, cool the reactor naturally to room temperature, wash with N,N-dimethylformamide (DMF), water and ethanol three times respectively, then collect the product by centrifugation, and dry it at 50°C to 100°C in a vacuum environment for 10 to 15 hours to obtain MIL-101 (Cr); S2. Preparation of MIL-101(Cr)-NO2: adding a certain proportion of MIL-101(Cr) to a mixture of concentrated H2SO4 and concentrated HNO3, stirring the mixture at 1°C to -2°C for 5 to 7 hours, pouring the mixture into ice water while stirring, and warming it to room temperature; washing the mixture with water and ethanol three times each, collecting the product by centrifugation, and drying it at 50°C to 100°C under vacuum for 10 to 15 hours to obtain MIL-101(Cr)-NO2; S3, preparation of r-GQDs: adding glucose in a certain proportion to deionized water to dissolve, transferring the solution to a reactor with a polytetrafluoroethylene liner after dissolution, and reacting at 150°C to 200°C for 4 to 5 hours; After the reactor is cooled, the collected solution is centrifuged to remove the precipitate, and the supernatant is poured into a beaker, a certain proportion of sodium borohydride is added, and the mixture is reduced by stirring with a magnetic stirrer at room temperature for 3 to 5 hours to obtain an r-GQDs solution; S4. Preparation of r-GQDs / MIL-101(Cr)-NO2: Take an appropriate amount of MIL-101(Cr)-NO2 and add it to the pretreated rGQDs solution with a pH value of 7 to 8, and then stir it at room temperature for 3 to 5 hours; after the reaction is completed, centrifuge it, then wash it twice with deionized water, and finally vacuum dry it at 60°C to 100°C for 10 to 13 hours to obtain the desired product.

2. The method for preparing the photocatalytic nitrate reduction ammonia production material MIL-101(Cr)-NO2rGQDs according to claim 1, characterized in that: The mass ratio of the terephthalic acid to Cr(NO3)3·9H2O is 1:2 to 1:

3.

3. The method for preparing the photocatalytic nitrate reduction ammonia production material MIL-101(Cr)-NO2rGQDs according to claim 1, characterized in that: The molar ratio of the ML-101(Cr) to the mixed solution of concentrated H2SO4 and concentrated HNO3 is 1:200 to 1:

250.

4. The method for preparing the photocatalytic nitrate reduction ammonia production material MIL-101(Cr)-NO2rGQDs according to claim 1, characterized in that: The mass ratio of the sodium borohydride to glucose is 1:5 to 1:

10.

5. The method for preparing the photocatalytic nitrate reduction ammonia production material MIL-101(Cr)-NO2rGQDs according to claim 1, characterized in that: The mass ratio of the MIL-101(Cr)-NO2 to rGQDs is between 1:3 and 1:8.